Sociodemographic patterning of dietary profiles among Inuit youth and adults in Nunavik, Canada: a cross-sectional study - Aker, Amira; Ayotte, Pierre; Furgal, Chris; Kenny, Tiff-Annie; Little, Matthew; Gauthier, Marie-Josée; Bouchard, Amélie; Lemire, Mélanie (Canadian Journal of Public Health, 2022)
Objectives Country (traditional) foods are integral to Inuit culture, but market food consumption is increasing. The Qanuilirpitaa? 2017 Nunavik Health Survey (Q2017) reported similar country food consumption frequency compared to that in 2004; however, examining food items individually does not account for diet patterns, food accessibility, and correlations between food items. Our objective was to identify underlying dietary profiles and compare them across sex, age, ecological region, and food insecurity markers, given the links among diet, health, and sociocultural determinants. Methods Food frequency and sociodemographic data were derived from the Q2017 survey (N = 1176). Latent profile analysis identified dietary profiles using variables for the relative frequencies of country and market food consumption first, followed by an analysis with those for country food variables only. Multinomial logistic regression examined the associations among dietary profiles, sociodemographic factors, and food insecurity markers (to disassociate between food preferences and food access). Results Four overall dietary profiles and four country food dietary profiles were identified characterized by the relative frequency of country and market food in the diet. The patterns were stable across several sensitivity analyses and in line with our Inuit partners’ local knowledge. For the overall profiles, women and adults aged 30–49 years were more likely to have a market food–dominant profile, whereas men and individuals aged 16–29 and 50+ years more often consumed a country food–dominant profile. In the country food profiles, Inuit aged 16–29 years were more likely to have a moderate country food profile whereas Inuit aged 50+ were more likely to have a high country food–consumption profile. A low country and market food–consumption profile was linked to higher prevalence of food insecurity markers. Conclusion We were able to identify distinct dietary profiles with strong social patterning. The profiles elucidated in this study are ...